ATTITUDINAL STANCE TOWARDS THE FREE NUTRITIOUS MEALS PROGRAM'S IMPLEMENTATION: AN APPRAISAL STUDY OF TEMPO.CO'S NEWS REPORT - Alyssa Myrelia Nafhanda; Eva Tuckyta Sari Sujatna; Susi Yuliawati (Lire Journal (Journal of Linguistics and Literature), 2025)
Drawing on the appraisal theory framework developed by Martin and White (2005), this study examines Tempo's attitudinal stance.co toward the Free Nutritious Meals Program (Program Makan Bergizi Gratis) implemented by the Indonesian government in 2025. The results show that a total of 63 attitudinal resources were identified, with appreciation being the most frequent (43%), followed by judgement (40%) and affect (17%). Negative attitudes account for 74% of the data, indicating a predominantly negative stance. These criticisms are explicitly conveyed and focus on operational issues such as food quality, safety concerns, limited menu variation, unequal distribution, and perceived weaknesses in government management. Positive attitudes (26%) are less frequent and focus mainly on the program’s intended goals, such as improving children’s nutrition and supporting local food industries, rather than its actual implementation. These findings indicate that Tempo.co tends to adopt a negative stance toward the program’s implementation, primarily expressed through explicit evaluations of its shortcomings, while offering limited recognition to its broader policy objectives